DVB‐S2X: extending DVB‐S2 flexibility for core markets and new applications. (9th November 2015) - Morello, Alberto; Mignone, Vittoria
Summary: Digital Video Broadcasting–Satellite–Second Generation (DVB ‐ S2) has been specified about 10 years ago, with a strong focus on Direct‐to‐Home, but interactive broadband applications (forward link), digital satellite news gathering and other professional links such as internet trunking were included. Since then, new requirements have come up, including extended efficiency and flexibility in the core applications of DVB‐S2, with specific focus on ultra‐high‐definition television delivery to the home, using High Efficiency Video Coding, the new video coding technique jointly developed by ITU and MPEG, and new ones for emerging markets. DVB‐S2X provides the necessary technical specifications for covering traditional DVB‐S2 use cases and new ones for operating at very low signal‐to‐noise ratio down to −10 dB, such as mobile services for business jets, fast trains and boats, and low aperture terminals for journalists. This paper and the others in this special issue describe the details of the standard and its performance in the various application scenarios. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : The paper introduces the novel Digital Video Broadcasting‐Satellite‐Second Generation (DVB‐S2) standard extensions, namely DVB‐S2X, providing additional technologies and features for improved performance. It targets the core applications of DVB‐S2, including Direct to Home, interactive broadband applications (forward link), contribution, digital satellite news gathering, and other professional links such as internet trunking. The specification also provides an extended operational range to cover emerging markets operating at very low signal‐to‐noise ratio down to 10 dB, such as mobile services for business jets, fast‐trains, and boats.